Identification of swine influenza A virus and Stenotrophomonas maltophilia co-infection in Chinese pigs - Hou Dongjun (Virology Journal, 2012)
Abstract Background Influenza virus virulence can be exacerbated by bacterial co-infections. Swine influenza virus (SIV) infection together with some bacteria is found to enhance pathogenicity. Methods SIV-positive samples suspected of containing bacteria were used for bacterial isolation and identification. Antimicrobial susceptibility testing was performed by disc diffusion methods. To investigate the interaction of SIV and the bacteria in vitro, guinea pigs were used as mammalian hosts to determine the effect on viral susceptibility and transmissibility. Differences in viral titers between groups were compared using Student’s t-test. Results During surveillance for SIV in China from 2006 to 2009, seven isolates (24.14%) of 29 influenza A viruses were co-isolated with Stenotrophomonas maltophilia from nasal and tracheal swab samples of pigs. Antimicrobial susceptibility testing showed that the bacteria possessed a high level of resistance towards clinically used antibiotics. To investigate the interaction between these two microorganisms in influencing viral susceptibility and transmission in humans, guinea pigs were used as an infection model. Animals were inoculated with SIV or S. maltophilia alone or co-infected with SIV and S. maltophilia. The results showed that although no transmission among guinea pigs was observed, virus–bacteria co-infections resulted in higher virus titers in nasal washes and trachea and a longer virus shedding period. Conclusions This is the first report of influenza virus co-infection with S. maltophilia in the Chinese swine population. Increased replication of virus by co-infection with multidrug resistant bacteria might increase the infection rate of SIV in humans. The control of S. maltophilia in clinics will contribute to reducing the spread of SIV in pigs and humans.